Clinical Features, Treatment and Monitoring in Patients With Polymyalgia Rheumatica - Fatma Gül YURDAKUL,; Hatice BODUR,; Filiz SİVAS,; Bedriye BAŞKAN,; Filiz ESER,; Onur YILMAZ, (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate the clinical symptoms and laboratory findings of Turkish patients with polymyalgia rheumatica. Patients and methods: Clinical data of 41 patients (9 males, 32 females; mean age 65.5±7.6 years; range 60 to 80 years) with polymyalgia rheumatica were retrospectively evaluated. Patients’ clinical symptoms, laboratory findings, therapies and therapeutic responses were analyzed. Results: The most common symptoms were bilateral shoulder pain (59.9%) and morning stiffness (48.78%). Mean erythrocyte sedimentation rate at diagnosis was 66.8±22.5 mm/h, while mean C-reactive protein value was 48.7±25.8 mg/dL. In the third week of corticosteroid treatment, good response to treatment was detected in 33 patients (80.5%). Mean age of patients who gave good response to treatment (67.2±6.7) was higher than mean age of patients who gave poor or no response to treatment (58.5±7.8) (p=0.009). Conclusion: Patients’ clinical features, laboratory findings, initial steroid doses, and responses to corticosteroid therapy were consistent with the literature. However, the rate of morning stiffness was high and peripheral arthritis was rare. Giant cell arteritis was not detected in patients with polymyalgia rheumatica. Good response to early steroid treatment was observed in older patients. Rate of relapse was low. Further studies are required to evaluate factors affecting response to treatment, remission, and relapse.